2013
DOI: 10.1097/sap.0b013e31824f220e
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Epidural and Spinal Anesthesia With Ischemia-Reperfusion Injury on the Rat Transverse Rectus Abdominis Musculocutaneous Flap

Abstract: The purpose of this study is to compare the effects of spinal and epidural anesthesia on a rat transverse rectus abdominus myocutaneous flap ischemia-reperfusion injury model.Forty Sprague-Dawley rats were divided into 4 experimental groups: group I (n = 10), sham group; group II (n = 10), control group; group III (n = 10), epidural group; and group IV (n = 10), spinal group. After the elevation of the transverse rectus abdominus myocutaneous flaps, all groups except for the sham group were subjected to normot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…IRI may occur in such case according to ischemia time and replanted size. It was stated that neuroaxial block enables a decrease in ischemiareperfusion injuries in the muscle flaps [5].…”
Section: Discussionmentioning
confidence: 99%
“…IRI may occur in such case according to ischemia time and replanted size. It was stated that neuroaxial block enables a decrease in ischemiareperfusion injuries in the muscle flaps [5].…”
Section: Discussionmentioning
confidence: 99%
“…Hamilton 100 μL gas-tight syringes were advanced 15 mm through the polyethylene tube using a 28-gauge needle. An injection of 2% lidocaine [Aritmal ® , Osel İlaç San ve Tic AŞ, Istanbul, Turkey] 25 μL solution was administered (Acar et al, 2013).…”
Section: Methods Of Spinal Anesthesiamentioning
confidence: 99%
“…Menting et al reported that repetitive administration of isoflurane daily, exerted a protective effect against renal I/R injury while single-dose isoflurane did not have the same effect [10]. Acar et al compared the protective effects of spinal and epidural anesthesia against I/R injury created in transverse rectus abdominis muscle and reported that epidural anesthesia is superior to spinal anesthesia in preventing I/R injury [11].…”
Section: оригінальні наукові роботиmentioning
confidence: 99%